Historical-Discursive Analysis of the Editorial "1964" in Folha de São Paulo - da Silva Santos, Cynthia Adrielle; Costa, Alessandra; Silva Saraiva, Luiz Alex (Organizações & Sociedade, 2024)
The article aims to analyze the Folha de São Paulo editorial "1964" in the light of the historicaldiscursive approach (HDA), basing the discussion on the concepts of discourse, media and history, and the historiography of the press and dictatorship. This text, published on March 30, 2014, on the eve of the 50th anniversary of the 1964 coup, is part of a broader movement that also includes other newspapers of the mainstream press to reassess and rewrite their history during the period of the Brazilian military dictatorship (1964-1985). The methodology used was the eight stages of the HDA and its five central questions. By identifying three dichotomous macro-topics (support for the military dictatorship as a mistake versus support as a long and painful learning process; the regime’s violence versus its economic achievements; and the dispute between revolutionary socialism versus the market economy) and the discursive strategies used (predication, argumentation, perspective, intensification, and mitigation), it was possible to observe that the newspaper discursively: (a) makes the problems caused by the military regime invisible; (b) emphasizes the economic growth that the country experienced during the period; and (c) justifies its actions by linking them to the context of the time, which raises questions about the examination of its position. The main conclusions suggest that the ambiguity with which the company positions itself, attenuating its contribution to the military regime and at the same time intensifying its democratic role, makes sense in the light of a contextualized business strategy and should be considered in the discussion about the interfaces between discourse, media and history.